Coordination of Ubiquinol Oxidase and Cytochrome cbb(3) Oxidase Expression by Multiple Regulators in Rhodobacter capsulatus - Swem, Danielle L. (American Society for Microbiology, 2002)
Rhodobacter capsulatus utilizes two terminal oxidases for aerobic respiration, cytochrome cbb(3) and ubiquinol oxidase. To determine the transcription factors involved in terminal oxidase expression, ccoN-lacZ and cydA-lacZ protein fusions were assayed in a variety of regulatory mutants. The results of this and previous studies indicate that cytochrome cbb(3) expression is controlled by regB-regA, fnrL, and hvrA and that ubiquinol oxidase expression is controlled by regB-regA, fnrL, hvrA, crtJ, and aerR.